Disease-specific survival of malignant melanoma after Mohs micrographic surgery is not impacted by initial margins: A systematic review and meta-analysisCapsule Summary - Olivia M. Crum, MD; Elliott H. Campbell, MD; Cynthia J. Chelf, MLS, AHIP; Addison M. Demer, MD; Jerry D. Brewer, MD, MS (Elsevier, 2023)
Background: During Mohs surgery for melanoma, evidence has demonstrated that many surgeons opt for smaller initial margins than traditionally recommended (0.5 cm for in situ and 1 cm for invasive). Literature regarding surgical outcomes based on initial margin is sparse. Objective: To determine differences in disease-specific survival of melanoma after Mohs micrographic surgery for varied initial surgical margins. Methods: A literature search was conducted on February 14, 2022, from MEDLINE via PubMed (1946-present), Embase (1974-present), Central (1991-present), and Scopus (1960-present). The primary outcome was disease-specific mortality. Results: Nineteen studies were included for final analysis. The overall disease-specific mortality rate of melanoma in all included studies was 0.5% (CI, 0.1-0.8; P, .010). Disease-specific mortality for 1 to 5, 5, and 6 to 10 mm categories were 0.4% (CI, 0.0-0.9; P, .074), 0.7% (CI, 0.2-1.3; P, .2-1.3), and 0.4% (CI, -0.9 to 1.8; P, .524), respectively. None of the variances across initial margin categories were statistically significant. Limitations: Early-stage melanomas have low overall mortality rates. In our associated article, initial margins of 5 to 10 mm were shown to have the lowest rates of local recurrence. Conclusions: In this systematic review and meta-analysis, melanoma-specific mortality was not significantly impacted by the initial surgical margin taken during Mohs micrographic surgery.